The Perceptions of Middle - Aged About Physical Activity Related Incident Prediabetes - Sumandar Sumandar; Rohmi Fadhli; Muhammad Firdaus (Universitas STRADA Indonesia, 2019)
Diabetes mellitus is a metabolic disorder characterized by the presence of hyperglycemia due to defective insulin secretion, defective insulin action or both. State they have a high risk of chronic illness and low health status caused by bad behaviors such as physical activity.The study aim was to determine correlation perceptions of middle-aged about physical activity toward incident prediabetes. The Sample of 54 participants selected by using cluster sampling and cross-sectional method.Bivariate analysis data was by using chi-square analysis.There were 29,6% middle-aged had been incident prediabetes. The conclusion of this research there was perceptions relation between perceptions with incident pre-diabetes (p-value 0,002;OR; 0,118).This study recommends to community health nurse in quality improvement such as attending workshop,training,exchange of nurse,changing the design education and health promotion, Focus group discussion with them.Service excellent will be reflected to decrease prediabetes, so that degree of health and maintain can be achieved.Further can build post health service.